Subsidi pemerintah dan rent-seeking : efisiensi investasi perusahaan BUMN di Indonesia - Lisa Kurnia; Farah Margaretha Leon (Jurnal Riset Pendidikan Ekonomi, 2023)
Government subsidy is one of the policy interventions to support economic growth and development. In developing countries, including Indonesia, the subsidy is vital for companies, especially State-Owned Enterprise (SOE), to increase investment efficiency. However, one way for the company to obtain a government subsidy is through the rent-seeking process. Therefore, this study is trying to investigate the significance of government subsidy and the rent-seeking process to investment efficiency. The independent variables in this study are the government subsidy and the rent-seeking process, while the investment efficiency is the dependent variable. This study also uses four control variables, return on asset (ROA), return on equity (ROE), growth, and board size. This research use data from 12 SOEs out of 109 SOEs for eight years (2013-2020) and utilised multivariable regression to analyse that. This study shows that government subsidy, rent-seeking, growth, and board size does not significantly affect investment efficiency.On the other hand, ROA and ROE have a significant negative relationship with investment efficiency. The finding from this study could be used for SOEs to optimise the government subsidy for investment efficiency. This study also uses the natural logarithm of cash given to the government to measure the rent-seeking variable as a novelty which differentiates from other studies.